Dietary Lipid Requirements of Juvenile Malaysian Mahseer (Tor Tambroides Bleeker) - Ramezani Fard, Ehsan (2011)
This study was carried out to determine the effects of dietary lipid level and source on the growth performance and tissue fatty acid profile of juvenile Malaysian mahseer, Tor tambroides. An attempt was also made to determine the best dietary lipid composition in term of different fatty acid ratios for this species. Domesticated wild caught mahseer juveniles were used in all feeding trials. In the first two experiments, four isonitrogenous diets with fish oil as the major source of the oil were formulated in order to provide different dietary lipid levels (5, 10, 15 and 20% as fed basis). In the first experiment, the effects of these diets on the growth performance and final fatty acid composition of fish tissues were studied while in the second experiment, the changes over a six-week time of muscle fatty acid composition were evaluated. In the third experiment, fish oil was substituted by palm oil, sunflower oil and linseed oil at 50% and 100% ratio. A diet including 100% fish oil (% of total oil in the diet) was also used as a control. In the fourth experiment, juveniles were fed four test diets with a same basal composition but mixed with different oils in a 2×2 factorial experimental design. The two factors were the levels of dietary saturated fatty acid and dietary n–3 polyunsaturated fatty acids (PUFA). In the last experiment, three isonitrogenous diets were formulated to contain different linolenic acid/linoleic acid ratios. A diet containing 100% palm oil was also used as a control. At the end of all the experiments, main growth performance variables of fish were estimated. The whole body proximate composition as well as muscle and liver fatty acid profiles were also determined. The growth of fish linearly decreased with the increase of dietary lipid and the best performance of Tor tambroides juveniles was achieved at 5% dietary lipid. However, reduction of n–3 PUFA content of fish muscle after six weeks may show that a diet containing high level of n–3 PUFA cannot meet all the essential fatty acid requirements of T. tambroides. Replacement of dietary fish oil with palm oil improved the growth performance. However, percentage of replacement had no significant effect (P>0.05) on the growth. Tor tambroides fed a diet containing low amount of n–3 PUFA (2%) and high amount of saturated fatty acid (38%) showed the best growth performance. Polynomial regression analysis between the ratios of saturated to n–3 fatty acid in the diet and final weight gain of fish showed a maximum weight gain at the highest ratio of 15.3. The significant interaction (P<0.05) between dietary saturated fatty acid and n–3 PUFA levels was observed for the total n–3 PUFA content of both muscle and liver tissues indicating a tissue n–3 sparing action by dietary saturated fatty acid. The increase of dietary linolenic acid to linoleic acid ratio did not improve the growth performance of T. tambroides. It can be concluded that a diet containing 5% crude lipid with a saturated fatty acid to n–3 ratio of 15.3 and a minimum n–3 PUFA content of 2.5% (of total fatty acid) can provide the best growth performance, and efficiently maintain the muscle n–3 PUFA content of mahseer juveniles.